The Automatic Monitoring System for 3D-CEMBSv2 in the Operational Version - Dzierzbicka-Glowacka, Lidia; Nowicki, Artur; Janecki, Maciej (Journal of Environmental Science and Engineering Technology, 2013)
The objective of this paper is to present the development of an automatic monitoring system for the model 3DCEMBSv2 (Coupled Ecosystem Model of the Baltic Sea, version 2) in the operational mode. The predictive, ecohydrodynamic model 3D-CEMBS will be used as an appropriate tool to control the conditions and bioproductivity of the Baltic environment and to forecast physical and ecological changes in the studied basin. 3D-CEMBSv2 provides hydrodynamic forecast of such variables as: temperature, salinity, sea surface height, currents, ice area cover and thickness. 3D-CEMBS model is also equipped with the ecosystem module that covers 3 phytoplankton groups, nutrients (nitrate, ammonia, phosphate, silicate), zooplankton, dissolved oxygen and small pelagic detritus. The automatic monitoring system also provides a 48-hour forecasts of above parameters that are available on the models website. Atmospheric forcing is supplied by the UM model of the Interdisciplinary Centre for Mathematical and Computational Modelling of the Warsaw University.